2000
DOI: 10.1034/j.1600-0447.2000.101001029.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized anxiety disorder (ICD‐10) in primary care from a cross‐cultural perspective: a valid diagnostic entity?

Abstract: It remains questionable whether the current ICD-10 diagnosis of GAD defining 6 months as a minimum duration and requiring at least four associated symptoms for diagnosis is the most appropriate option. Using this definition, a substantial proportion of psychosocially disabled subjects characterized by anxiety, tension and worrying remain undetected, and are possibly therefore not adequately treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
2
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 0 publications
7
81
2
5
Order By: Relevance
“…This is supported by indications that some cases falling below the GAD threshold are sufficiently similar to diagnosed cases that their inclusion may improve the validity of the diagnosis. Important similarities have previously been observed in functional impairment, socio-demographic features, family history of GAD, and other key correlates between the full GAD syndrome and GAD lasting as little as one month (Bienvenu et al, 1998;Carter et al, 2001;Hunt et al, 2002;Kendler et al, 1992;Kessler et al, 2005b;Maier et al, 2000;Wittchen et al, 2002) or involving non-excessive worry (Bienvenu et al, 1998;Ruscio et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…This is supported by indications that some cases falling below the GAD threshold are sufficiently similar to diagnosed cases that their inclusion may improve the validity of the diagnosis. Important similarities have previously been observed in functional impairment, socio-demographic features, family history of GAD, and other key correlates between the full GAD syndrome and GAD lasting as little as one month (Bienvenu et al, 1998;Carter et al, 2001;Hunt et al, 2002;Kendler et al, 1992;Kessler et al, 2005b;Maier et al, 2000;Wittchen et al, 2002) or involving non-excessive worry (Bienvenu et al, 1998;Ruscio et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…In the Australian National Survey of Mental Health and Well-Being sample, Slade and Watson [2006] found similarly high tetrachoric correlations for GAD and panic disorder (.62), agoraphobia (.61), and social anxiety disorder (.58), which were not well distinguished from the associations between social anxiety disorder and panic disorder (.59). Consistent with these reported rates, Maier et al [2000] examined the role of the autonomic symptoms that comprise the diagnosis of GAD in ICD-10 (but were removed from DSM-IV) and found that there were strong relationships between these symptoms and persistent worry and anxiety. These relationships suggest that, at least for a subgroup of individuals with GAD, fear processes may be an important component of their anxious presentation.…”
Section: Symptomatic Overlap Between Gad and Other Anxiety Disorders:mentioning
confidence: 76%
“…[81] A number of studies have shown that a lower duration threshold (e.g., 1 month, 3 months) would identify respondents with similar symptom severity and clinical impairment to the current 6-month threshold (WHO Psychological Problems in Primary Care; NCS-R; Zurich Cohort Study). [79,82,83] Requiring a longer duration requirement (e.g., 12 months), however, would identify respondents with more severe and impairing symptoms than are found in DSM-IV GAD (WMHS). [78] Moreover, variations in the duration threshold would not substantially influence the type of person identified in DSM-V in terms of demographics (ECA; NCS-R; Zurich Cohort Study); [79,83,84] age of onset (WMHS); [78] familial risk of GAD (Virginia Twin Registry; NCS-R; EDSP); [77,85,86] or comorbidity profiles (ECA; Zurich Cohort Study; WMHS; EDSP).…”
Section: Dsm-v Options For ''A Number Of Events or Activities''mentioning
confidence: 99%